Internal Subseasonal Variability in the South China Sea Revealed by Eddy‐Resolving Numerical Simulations. Issue 4 (4th April 2020) - Xie, Juncheng; Zhou, Lei; Murtugudde, Raghu; Jochum, Markus; Zhong, Yisen
Abstract: Oceanic subseasonal variabilities in the South China Sea (SCS) derive from both external forcing and internal variability. There have been extensive studies on a range of external forcings, which are composed of local and remote components. In this study, the internal subseasonal variabilities in SCS are examined using an eddy‐resolving model. It is found that the internal subseasonal variabilities are pronounced in the northern SCS, which account for about half of total observed subseasonal variabilities. Particularly to the west of Luzon Strait, the internal subseasonal variabilities are enhanced on the periphery of a ring region. On the contrary, internal subseasonal variabilities are minimal in the center, which is mainly attributable to an upscale energy transfer. As a result, a mean jet is generated which transports heat and eddy kinetic energy along the edge of the ring region. We posit that the impact of internal subseasonal variabilities is significant for the background state in the region where the intense tropical cyclones occur over the northern SCS every year. Plain Language Summary: The internal subseasonal variabilities in a regional ocean are the variabilities caused by the internal oceanic processes. They are distinct from a direct response to external forcings. In the South China Sea (SCS), there have been extensive studies on oceanic subseasonal variabilities deriving from a range of external forcings. In this study, internal subseasonal variabilities are examined using a regional ocean model, which has a sufficient resolution to capture mesoscale eddies which have a typical spatial scale of hundreds of kilometers. The internal subseasonal variabilities are pronounced in the northern SCS, particularly to the west of Luzon Strait. The internal subseasonal variabilities are enhanced on the periphery of a ring region, while they are minimum in the center. In the ring region, energy is transferred from small scales to large scales, which is not common in the ocean. We posit that the impact of internal subseasonal variabilities is significant for the background state in the region where the intensive tropical cyclones occur over the northern SCS every year. Such process understandings are critical for establishing the sources of predictability and for advancing predictive understanding. Key Points: Internal subseasonal variability accounts for about half of total subseasonal variabilities in the northern South China Sea In a ring region to the west of Luzon Strait, the internal subseasonal variability is low in the center but enhanced on the periphery Upscale energy transfer leads to a mean jet around the ring region, which transfers heat and kinetic energy along the circumference